Specification of downlink-fixed reference channel DL-FRC for 5G new radio technology - Fatima Faydhe Al-Azzwi; Ruaa Ali Khamees; Zina Abdul Lateef; Batool Faydhe Al-Azzawi (Institute of Advanced Engineering and Science, 2022)
The next generation for mobile communication is new radio (NR) that supporting air interface which referred to the fifth generation or 5G. Long term evolution (LTE), universal mobile telecommunications system (UMTS), and global system for mobile communication (GSM) are 5G NR predecessors, also referred to as fourth generation (4G), third generation (3G) and second generation (2G) technologies. Pseudo-noise (PN) code length and modulation technique used in the 5G technology affect the output spectrum and the payload of DL-FRC specification, in this paper quadrature phase shift keying (QPSK), 16 QAM modulation approaches tested under additive white Gaussian noise (AWGN) in term of bit error rate (BER) which used with 5G technology system implemented with MATLAB-Simulink and programing and, resulting of 1672, 12296 bit/slot payload at frequency range FR1 from 450 MHz-6 GHz and 4424, 20496 bit/slot payload at frequency range FR2 from 24.25 GHz-52.6 GHz, also determining subcarrier spacing, allocated source block, duplex mode, payload bit/slot, RBW (KHz), sampling rate (MHz), the gain and the bandwidth of main, side loop where illustrated.